TINJAUAN YURIDIS TENTANG PENJATUHAN HUKUMAN MATI TERHADAP PERANTARA JUAL BELI NARKOTIKA YANG DISERTAI DENGAN PENCUCIAN UANG (STUDI PUTUSAN NOMOR 594/PID.SUS/2015/PN. TJB) - IKHWANUDDIN IKHWANUDDIN (JURNAL PROINTEGRITA, 2018)
This study aims to determine the decision of the constitutional court ruling Number 2-3 / PUU-V / 2007 concerning capital punishment in Indonesia in relation to the implementation of human rights in the 1945 Constitution, to find out what factors are obstacles to the application of capital punishment in Indonesia and to know how is the basic consideration of the judge in imposing the death sentence on the intermediary for the sale and purchase of narcotics accompanied by money laundering in Decision Number 594 / Pid.Sus / 2015 / PN. Tjb. Data collection method used is library research (library researc), namely by reviewing from various relevant literature sources and browsing reading sources, namely books, opinions of scholars, articles on the internet and downloading decisions from the decision directory site. The results showed the constitutional panel of judges stated that the death penalty in the Narcotics Law does not contradict the right to life guaranteed by the 1945 Constitution because the guarantee of human rights in the 1945 Constitution does not adhere to the principle of absoluteness. According to the Court, the basic rights guaranteed by articles 28A to 28I of the 1945 Constitution have been locked by article 28J which functions as a limit. Constraints to the execution of a number of convicts, namely juridical constraints with the Constitutional Court's decision to cancel the maximum limit for filing a one-year pardon, then the Constitutional Court's ruling that allows the submission of legal review (PK) may be more than once, as well as the presence of negative respondents from the public death penalty. The defendant committed his crime in an organized manner, including providing means of transporting narcotics and money laundering, imposing capital punishment was appropriate. His criminal act has been punished twice (resivided), and the last criminal act has also been carried out three times and then caught and tried (concurs). The defendant from the prison also continued to coordinate the provision of transportation of narcotics from Malaysia to Indonesia. The defendant has been difficult to be rehabilitated, so the only criminal that can stop the defendant is Death Crime.